TELAAH INFESTASI LIPAS (INSECTA: DICTYOPTERA) PADA BUS DAN KAITANNYA DENGAN PENGELOLAAN MODA TRANSPORTASI - Ari Tjahyadi Rafiuddin; Upik Kesumawati; Susi Soviana (JURNAL KAJIAN VETERINER, 2019)
The purpose of this research was to identify the cockroach species infesting public buses, determining its distribution and its infestation degree, and analyze the factors causing its infestation. The observation of the existence of cockroach was performed on 30% of buses found in 6 bus pool in Bogor City. Observations was focused on 6 sites inside the bus: 1) seats, 2 floor), 3) gaps, 4) shelves, 5) window, and 6) toilets. Cockroach were manually colletcted put in a labeled plastic pouchs. Observations was done within 30 minutes each bus. The degree of cockroach infestation was scored as zero, light, moderate, high, and very high infestation. The factors causing cockroach infestation in public buses measured using an enclosed questionnaire. A total number of 1626 individuals were collected identified as Blattella germanica cockroach (1353 individuals) and Periplaneta americana cockroach (273 individuals). The highest infestation of Blattella germanica was found in the buses in the pool-6 area with with average amount of 66.4 individuals per bus (very highly infested). While Periplaneta americana was found very highly infesting buses in the pool-5 area with average amount 25.3 individuals per bus. The cockroach infestation spreading in the gap (48.68%) with the highest number for the presence of both species. The shelves found as site with lowest infestation (12.60%). There was a weak correlation between cockroach infestation in the pool bus area with personal biosecurity (r = -0.116), medium relationship with places/equipment biosecurity (r = -0.406), and strong correlation with environmental biosecurity (r = -0.841).